2017
DOI: 10.1038/icb.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

p38α regulates cytokine‐induced IFNγ secretion via the Mnk1/eIF4E pathway in Th1 cells

Abstract: The p38 mitogen-activated protein kinase (MAPK) pathway is involved in the regulation of immune and inflammatory processes. We used p38α-conditional, p38β-deficient and p38α/β double-null mouse models to address the role of these two p38 MAPK in CD4 T cells, and found that p38α deficiency causes these cells to hyperproliferate. Our studies indicate that both p38α and p38β are dispensable for T helper cell type 1 (Th1) differentiation but, by controlling interferon (IFN)γ and tumor necrosis factor (TNF)α produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The case of T cells is interesting, as our data do not preclude a role for phospho-eIF4E in these cells when relieved from neutrophil suppression in the eIF4E S209A setting. Translational regulation of various cytokines by T cells reported in other contexts (37,39), as well as data of Webster et al (40) using the MNK inhibitor eFT508, support this notion. In contrast, work with T cells lacking MNKs has indicated that these kinases, and eIF4E phosphorylation, are dispensable for normal T-cell function, but indirectly affect their differentiation and activity, using an in vivo model of autoimmune encephalomyelitis (37,41), mirroring our own findings in the TME.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The case of T cells is interesting, as our data do not preclude a role for phospho-eIF4E in these cells when relieved from neutrophil suppression in the eIF4E S209A setting. Translational regulation of various cytokines by T cells reported in other contexts (37,39), as well as data of Webster et al (40) using the MNK inhibitor eFT508, support this notion. In contrast, work with T cells lacking MNKs has indicated that these kinases, and eIF4E phosphorylation, are dispensable for normal T-cell function, but indirectly affect their differentiation and activity, using an in vivo model of autoimmune encephalomyelitis (37,41), mirroring our own findings in the TME.…”
Section: Discussionmentioning
confidence: 53%
“…Several cell types, in addition to neutrophils, may be playing important roles that we did not observe in our mouse model. Possibilities include macrophages, in which eIF4E phosphorylation has been linked to cytokine production (36,37); regulatory T cells, where eIF4E levels have been implicated (38); and IFN-γ production by Th1 cells, which has recently been linked to the p38-MNK-eIF4E axis (39). The case of T cells is interesting, as our data do not preclude a role for phospho-eIF4E in these cells when relieved from neutrophil suppression in the eIF4E S209A setting.…”
Section: Discussionmentioning
confidence: 74%
“…The above-cited studies notwithstanding, little is known regarding translation regulatory events specific to the many different immune cell populations, particularly in the cancer-stroma context. eIF4E phos-phorylation appears to be important for the synthesis of cancer-relevant cytokines and chemokines, such as tumor necrosis factor α (TNF-α) and interferon γ (IFN-γ) (Andersson and Sundler 2006;Rowlett et al 2008;Herdy et al 2012;Salvador-Bernáldez et al 2017), and for the development of experimental autoimmune encephalomyelitis (Gorentla et al 2013). In neutrophils, eIF4E phosphorylation promotes survival and metastatic dissemination in a mouse model of breast cancer (Robichaud et al 2018).…”
Section: Immune Cellsmentioning
confidence: 99%
“…In human and mouse muscles, p38/Sty1 inhibition promotes the proliferation of quiescent satellite cells 46 . In activated lymphocytes, p38/Sty1 deficiency causes hyperproliferation, correlating with a decrease in eIF4E activity 47 . Thus, the S/MAPK mutants can successfully exit from the quiescent state at a lower threshold of environmental or physiological cues.…”
Section: Discussionmentioning
confidence: 99%